The Association between Social Activity and Health-Related Quality of Life in Yogyakarta, Indonesia - Baiq Wardatul Minan; Helfi Agustin (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Special Region of Yogyakarta is one of Province which has an old population structure in Indonesia. Total elderly are 45,000 or 13.81% of the total population. House for elderly (Rumah Sehat Lansia/ rusela) is a promotive and preventive program to improve the quality of life of the elderly in Yogyakarta. This study aimed to know the association between health related quality of life with social activity at Rusela Facility in Yogyakarta, Indonesia.Subjects and Method: This was a cross-sectional study conducted at Rumah Sehat Lansia, in Yogyakarta. The dependent variable was health-related quality of life. The independent variable was social activity. A sample of 87 elderly was selected purposively. The data were collected by interviews using a structured questionnaire. The data were analyzed by Chi square test.Results: Sample characteristic were female (78.20%) and 56-65 years old (57.50%). There was a positive association between social activity with health-related quality of life in elderly (OR= 6.85; 95%CI= 2.64 to 18.91; p<0.001).Conclusion: There is a positive association between social activity with health-related quality of life in elderly.Keywords: health-related quality of life, social activity, elderlyCorrespondence: Helfi Agustin. Department of Public Health, Ahmad Dahlan University, Yogyakarta, Jl. Prof. Dr. Soepomo, Janturan, Warungboto, Umbulharjo 55164, Yogyakarta. Email: helfiagustin@ikm.uad.ac.id. Mobile Phone: 085274554097.Journal of Health Promotion and Behavior (2020), 5(2): 87-95https://doi.org/10.26911/thejhpb.2020.05.02.03